Tunga and the poetic of (in)finitude:: Reflections on death in the game of the visual arts (TEL Tempo, Espaço e Linguagem, 2025)
This article seeks to reflect upon the matter of the finitude from the visual arts’ research field.  It will be carried out a reflection on the specificities and challenges in the academic study of the thematic of death by means of the poetics of the Brazilian artist Tunga. Tunga’s work “Semeando Sereias” (Seeding Sirens – 1987) will be investigated in the light of transdisciplinary approaches, as “poetic game” and as “photographic language”, in dialogue with the contingencies that are inherent to the study of artistic objects.